WTO Conference in Hong Kong: just the bare bones - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
The Sixth WTO Ministerial Conference in Hong Kong, held in December 2005, was reported as a modest but significant step in the current trade negotiation process...